2020
DOI: 10.3390/jcm9092909
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Benefit of Tamsulosin and the Hexanic Extract of Serenoa Repens, in Combination or as Monotherapy, in Patients with Moderate/Severe LUTS-BPH: A Subset Analysis of the QUALIPROST Study

Abstract: To investigate whether tamsulosin (TAM) and the hexanic extract of Serenoa repens (HESr) are more effective in combination than as monotherapy in men with moderate-to-severe lower urinary tract symptoms associated with benign prostatic hyperplasia (LUTS/BPH). Subset analysis of data from a 6-month, multicenter observational study. Patients received either tamsulosin (0.4 mg/day) or HESr (320 mg/day) alone or in combination. Primary endpoints were change in symptoms and quality of life. Tolerability was also as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…This aligns with our research results. However, previous studies did not subdivide the improvement of symptoms into storage and voiding, nor did they discuss the impact on sleep quality (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…This aligns with our research results. However, previous studies did not subdivide the improvement of symptoms into storage and voiding, nor did they discuss the impact on sleep quality (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, Alcaraz et al [12] reported their follow-up to the QUALIPROST study of 2016 [16] that compared HESr (Permixon) vs. tamsulosin vs. a combination of the two agents. The combination arm results were statistically superior related to IPSS, QoL, BII at p values of 0.002, 0.001, and 0.007, respectively (supplementary document at https: //www.mdpi.com/2077-0383/9/9/2909/sl, accessed on 30 July 2021).…”
Section: Hesr and Eesr Are Not Inferior To Tamsulosin Or To Finasteridementioning
confidence: 99%
“…This issue of degree of efficacy of LSESr based on the severity of the baseline IPSS warrants further scrutiny and, perhaps in a followup study, the authors of QUALIPROST will clarify this issue by comparing IPSS changes in the severe with the moderate LUTS cohorts. Notwithstanding, the 2020 QUALIPROST publication [12] and its supplement (URL provided earlier) are valuable contributions and raise the possibility of a synergistic effect of LSESr with the alpha-blocker tamsulosin.…”
Section: Lsesr Efficacy Is Greater In Severe Vs Moderate Lutsmentioning
confidence: 99%
“…In 2020, Alcaraz et al [9] reported their follow-up to the QUALIPROST study of 2016 [11] that compared HESr (Permixon) vs tamsulosin vs. a combination of the two agents. The combination arm results were statistically superior at p < 0.001.…”
Section: Hesr Not Inferior To Tamsulosin or To Finasteridementioning
confidence: 99%
“…This issue of degree of efficacy of LSESr based on the severity of the baseline IPSS warrants further scrutiny, and hopefully the corresponding author of the QUALIPROST study will clarify this issue by comparing the severe with the moderate LUTS cohorts. Notwithstanding, the 2020 QUALIPROST publication [9] and its supplement are valuable contributions and raise the possibility of a synergistic effect of LSESr with the alpha-blocker tamsulosin.…”
Section: Lsesr Efficacy Is Greater In Severe Vs Moderate Lutsmentioning
confidence: 99%